Social support perceived in family caregivers of people with chronic disease - Romero Guevara, Sandra Lucrecia; Correa, Bertha Lucia; Camargo Figuera, Fabio Alberto (Universidad y Salud, 2017)
Introduction: The increase in chronic diseases has put in evidence the problem between the supply and demand for health services, generating the displacement of care to home and the overload to family caregivers. Objective: To determine the social support perceived by family caregivers of people with chronic disease. Materials and Methods: A transversal study was conducted and the Inventory of Social Support on Chronic Disease of Hilbert instrument was used with 129 family caregivers of people with chronic disease seen in a hospital of third level of attention. Results: The caregivers are primarily women (89.9%). The average score of the scale was of 110.7, standard deviation = 38.1. Significant differences were found in the schooling (p=0.030), socioeconomic status (p=0.013) and the housing to the patient (p=0.010). Conclusion: The caregivers reported to be unhappy with perceived social support and this perception was related to the socio-economic conditions of the people.